Association between beauty standards shaped by social media and body dysmorphia among Egyptian medical students - Mohammed N. Abdelaziz; Ahmed R. A. Moustafa; Hajer Azzam; Anwar M. Bshar; Ismail S. Ismail; Omnia Yousry Elhadidy (Scientific Reports)
Abstract This study examines the relationship between exposure to unattainable beauty standards via social media and the prevalence of Body Dysmorphic Disorder among medical students in Egypt. The rapid development of digital platforms, particularly social media, has brought about a wider dissemination of unattainable beauty standards that may contribute to body image disorders and psychological problems. Given the unique pressures faced by medical students, who represent both consumers and influencers in health-related content, the current study attempts to ascertain whether excessive engagement with distorted beauty portrayals correlates with higher rates of BDD symptoms in this population. This was a cross-sectional questionnaire-based study consisting of 1126 undergraduate medical students, with a mean age of 20.8 years enrolled in any Egyptian medical school registered in the academic year 2023–2024, specifically from August–October 2024, except non-medical, graduate, and non-Egyptian students who met the exclusion criteria. We privately gathered answers via colleagues and electronically via online Google forms posted on social media groups. To our knowledge, this is the first study to investigate the relationship between social media use and BDD among medical students. According to social media practices, WhatsApp, Facebook, Instagram, YouTube, and TikTok were mostly used for 4–7 h daily. Most rarely or sometimes, take selfies, edit them with filters, and share them with others. The summary of BDDQ answers demonstrated that 6.3% of Egyptian medical students enrolled met the criteria for BDD. The majority reported that they do not like their face, and this leads to suffering from bullying in school or work, resulting in avoiding certain clothes as an avoidance behavior. The majority reported engaging in positive self-talk, participating in offline activities or hobbies, and unfollowing accounts promoting unattainable beauty standards as a coping strategy against unattainable beauty standards shaped by social media. Our study found that BDD is highly prevalent among social media users, especially on text-based platforms. The prevalence of BDD among Egyptian medical students is 6.3%, which is higher than worldwide. Interestingly, Egyptian medical students enrolled in our study believe that promoting body positivity, educating users about the risks of body dysmorphia, restricting content that promotes unrealistic body standards, and providing resources and support for those affected, respectively, are the critical measures that social media platforms should take to address body dysmorphia.